2019
DOI: 10.1177/0886260519867150
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Refuge: Adolescent Boys’ Experiences of Violence in “Post-Conflict” Colombia

Abstract: Increasingly, researchers and practitioners are examining connections between public and private cycles of violence. In complex emergency settings, these cycles of violence often intersect with conflicting norms and values as societies work toward sustainable peace. Gender norms, particularly norms of masculinity, are not often highlighted in transdisciplinary violence studies. Furthermore, few studies on either subject capture the perspectives and experiences of adolescent boys. This study seeks to explore ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The connections between women's experiences of violence in "private" and larger sociopolitical structures are made invisible, even if that violence is more frequent and sometimes more traumatic because of its intimate connotations (Skjelsbaek 2006). Relying on dichotomies of violencesuch as battlefront/homefront, extraordinary/everyday, or public/privaterisks leading to simplistic understandings with limited capacity to improve the lives of people living in war zones (Browne et al 2019;Gray 2016aGray , 2019Kirby 2015;McWilliams and Ni Aolain 2014). If the goal of peace initiatives is a positive peace, without any forms of physical and structural violence that could be causes of future conflict (Cockburn 2004;Galtung 1969), violence in intimate partnerships must be addressed alongside sexualized aggressions perpetrated by armed groups.…”
Section: Discussionmentioning
confidence: 99%
“…The connections between women's experiences of violence in "private" and larger sociopolitical structures are made invisible, even if that violence is more frequent and sometimes more traumatic because of its intimate connotations (Skjelsbaek 2006). Relying on dichotomies of violencesuch as battlefront/homefront, extraordinary/everyday, or public/privaterisks leading to simplistic understandings with limited capacity to improve the lives of people living in war zones (Browne et al 2019;Gray 2016aGray , 2019Kirby 2015;McWilliams and Ni Aolain 2014). If the goal of peace initiatives is a positive peace, without any forms of physical and structural violence that could be causes of future conflict (Cockburn 2004;Galtung 1969), violence in intimate partnerships must be addressed alongside sexualized aggressions perpetrated by armed groups.…”
Section: Discussionmentioning
confidence: 99%
“…When women are imagined as incapable of making war and thus as illegitimate targets of fighting, women who enter military ranks are unlikely to receive the socialization and training that fosters resilience among male soldiers. By extension, men failing to live up to ideals of militarized masculinity may similarly be denied acceptance, camaraderie, and other resources that support mental health and resilience (Browne et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, war can legitimize hyper-masculinity; exacerbating and normalizing violence when men seek or are expected to (re)assert masculinity in instances of community of familial vulnerability (Browne et al, 2019;Gibbs et al, 2020). This hyper-masculine aggression may become not only relatively more acceptable, but an adaptive behavior (Annan & Brier, 2010;Clark et al, 2010;Hudson et al, 2020;Saile et al, 2014;Vinck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A much wider qualitative literature exists for Colombia and the drivers related to IPV among those experiencing forced displacement there (Browne et al, 2019;Wirtz, 2014;Alzate, 2018;Friedemann-Sánchez & Lovatón, 2012;Hynes, 2012;Hynes et al, 2016;Jones & Ferguson, 2009;Noe & Rieckmann, 2013). This literature includes a study that found over 50% of displaced women had suffered physical IPV versus 20% of non-displaced women in Colombia (Alzate, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation